ESTABLISHMENT OF SOIL STRENGTH PARAMETERS FROM STANDARD PENETRATION TEST (SPT)AND ELECTRICAL RESISTIVITY METHOD - HATTA, KHAIRUL ANWAR (2015)
The strength parameter of soil is the most important aspect of ground engineering. Therefore, precise determination of engineering parameters of soil is essential for many calculation purposes in geotechnical engineering design such as ground bearing capacity and ground slope stability. Soil investigation (SI) incorporating bore hole sampling provides the most reliable value of the relevant soil parameters for the purpose of geotechnical design, yet it is time-consuming, expensive and destructive. As an alternative, geophysical method has been found to be an attractive tool for delineating of subsurface properties without soil disturbance. The primary objective of this research work is to investigate the relationship between electrical resistivity and various soil parameters. The research work consists of field resistivity surveys, soil boring and soil characterization tests. Field survey includes ID vertical electrical sounding (VES) and 2D resistivity imaging for comparison.